An Analysis of English Teacher’s Teaching Strategy in English in New Normal Era (A Study Conducted at SMA Negeri 1 Telaga) - Sindi Ivanka Towapo; Sartin T. Miolo; Nurlaila Husain (Transbahasa, 2025)
This study explores the teaching strategies employed by English teachers at SMAN 1 Telaga in adapting to the